Black carbon emissions from in-use ships: a California regional assessment - Buffaloe, G. M.; Lack, D. A.; Williams, E. J.; Coffman, D.; Hayden, K. L.; Lerner, B. M.; Li, S. -M.; Nuaaman, I.; Massoli, P.; Onasch, T. B.; Quinn, P. K.; Cappa, C. D. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2014)
Black carbon (BC) mass emission factors (EFBC; g BC (kg fuel)(-1)) from a variety of ocean-going vessels have been determined from measurements of BC and carbon dioxide (CO2) concentrations in ship plumes intercepted by the R/V Atlantis during the 2010 California Nexus (CalNex) campaign. The ships encountered were all operating within 24 nautical miles of the California coast and were utilizing relatively low sulphur fuels (average fuel sulphur content of 0.4%, 0.09% and 0.03% for vessels operating slow-speed, medium-speed and high-speed diesel engines, respectively). Black carbon concentrations within the plumes, from which EFBC values are determined, were measured using four independent instruments: a photoacoustic spectrometer and a particle soot absorption photometer, which measure light absorption, and a single particle soot photometer and soot particle aerosol mass spectrometer, which measure the mass concentration of refractory BC directly. These measurements have been used to assess the level of agreement between these different techniques for the determination of BC emission factors from ship plumes. Also, these measurements greatly expand upon the number of individual ships for which BC emission factors have been determined during real-world operation. The measured EFBC's have been divided into vessel type categories and engine type categories, from which averages have been determined. The geometric average EFBC (excluding outliers) determined from over 71 vessels and 135 plumes encountered was 0.31 +/- 0.31 gBC (kg fuel)(-1), where the standard deviation represents the variability between individual vessels. The most frequent engine type encountered was the slow-speed diesel (SSD), and the most frequent SSD vessel type was the cargo ship sub-category. Average and median EFBC values from the SSD category are compared with previous observations from the Texas Air Quality Study (TexAQS) in 2006, during which the ships encountered were predominately operating on high-sulphur fuels (average fuel sulphur content of 1.6 %). There is a statistically significant difference between the EFBC values from CalNex and TexAQS for SSD vessels and for the cargo and tanker ship types within this engine category. The CalNex EFBC values are lower than those from TexAQS, suggesting that operation on lower sulphur fuels is associated with smaller EFBC values.